Nuclear targeting peptide-modified, DOX-loaded, PHBV nanoparticles enhance drug efficacy by targeting to Saos-2 cell nuclear membranes. Issue 5 (24th March 2018) - Şahin, Ayla; Eke, Gozde; Buyuksungur, Arda; Hasirci, Nesrin; Hasirci, Vasif
Abstract: The aim of this study was to target nano sized (266 ± 25 nm diameter) poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) particles carrying Doxorubicin (DOX), an anticancer agent, to human osteosarcoma cells (Saos-2). A nuclear targeting molecule (Nuclear Localization Signal, NLS), a 17 a.a. peptide, was attached onto the doxorubicin loaded nanoparticles. NLS conjugated nanoparticles surrounded the cell nuclei, but did not penetrate them. Free doxorubicin and doxorubicin loaded nanoparticles entered the cytoplasm and were evenly distributed within the cytoplasm. The localization of the NLS-targeted particles around the nuclear membrane caused a significantly higher decrease in the cancer cell numbers due to apoptosis or necrosis than the untargeted and free doxorubicin formulations showing the importance of targeting the nanoparticles to the nuclear membrane in the treatment of cancer.